Longitudinal associations between youth tobacco and substance use in waves 1 and 2 of the Population Assessment of Tobacco and Health (PATH) Study. (1st October 2018) - Silveira, Marushka L.; Conway, Kevin P.; Green, Victoria R.; Kasza, Karin A.; Sargent, James D.; Borek, Nicolette; Stanton, Cassandra A.; Cohn, Amy; Hilmi, Nahla; Cummings, K. Michael; Niaura, Raymond S.; Lambert, Elizabeth Y.; et al.
Highlights: Any tobacco use predicted subsequent substance (alcohol or drug) use. E-cigarette use predicted substance use except non-prescribed painkillers/sedatives. Substance use consistently predicted tobacco use across products. Marijuana use predicted use of all tobacco products except smokeless tobacco. Targeting risk factors shared across tobacco and substances may be beneficial. Abstract: Background: While evidence suggests bidirectional associations between cigarette use and substance (alcohol or drug) use, how these associations are reflected across the range of currently available tobacco products is unknown. This study examined whether ever tobacco use predicted subsequent substance use, and ever substance use predicted subsequent tobacco use among 11, 996 U.S. youth (12–17 years) from Waves 1 (2013–2014) and 2 (2014–2015) of the Population Assessment of Tobacco and Health (PATH) Study. Methods: Ever use of cigarettes, e-cigarettes, traditional cigars, cigarillos, filtered cigars, pipe, hookah, snus pouches, smokeless tobacco excluding snus pouches, dissolvable tobacco, bidis, kreteks, alcohol, marijuana, prescription drugs, and other drugs (cocaine and other stimulants, heroin, inhalants, solvents, and hallucinogens) was assessed at Wave 1 followed by past 12-month use assessments at Wave 2. The analyses included covariates (demographics, mental health, sensation seeking, prior use) to mitigate confounding. Results: Ever tobacco use predicted subsequent substance use. The magnitude of the associations was lowest for alcohol, higher for marijuana, and highest for other drugs. Ever substance use also predicted subsequent tobacco use. Specifically, ever alcohol, marijuana, and non-prescribed Ritalin/Adderall use predicted tobacco-product use. Ever e-cigarette and cigarette use exclusively and concurrently predicted subsequent any drug (including and excluding alcohol) use. E-cigarette and cigarette use associations in the opposite direction were also significant; the strongest associations were observed for exclusive cigarette use. Conclusion: Tobacco and substance use prevention efforts may benefit from comprehensive screening and interventions across tobacco products, alcohol, and drugs, and targeting risk factors shared across substances.